Procedural generation of aesthetic patterns from dynamics and iteration processes - Gdawiec, Krzysztof (Zielona Góra: Uniwersytet Zielonogórski)
Aesthetic patterns are widely used nowadays, e.g., in jewellery design, carpet design, as textures and patterns on wallpapers, etc. Most of the work during the design stage is carried out by a designer manually. Therefore, it is highly useful to develop methods for aesthetic pattern generation. In this paper, we present methods for generating aesthetic patterns using the dynamics of a discrete dynamical system. The presented methods are based on the use of various iteration processes from fixed point theory (Mann, S, Noor, etc.) and the application of an affine combination of these iterations.
Keywords: dynamical systems; dynamics; iteration process; aesthetic pattern